Promising Immunotherapeutic Modalities for B-Cell Lymphoproliferative Disorders - Mihályová, Jana; Hradská, Katarína; Jelínek, Tomáš; Motais, Benjamin; Celichowski, Piotr; Hájek, Roman (International journal of molecular sciences, 2021)
Over the last few years, treatment principles have been changed towards more targeted therapy for many B-cell lymphoma subtypes and in chronic lymphocytic leukemia (CLL). Immunotherapeutic modalities, namely monoclonal antibodies (mAbs), bispecific antibodies (bsAbs), antibody-drug conjugates (ADCs), and chimeric antigen receptor T (CAR-T) cell therapy, commonly use B-cell-associated antigens (CD19, CD20, CD22, and CD79b) as one of their targets. T-cell engagers (TCEs), a subclass of bsAbs, work on a similar mechanism as CAR-T cell therapy without the need of previous T-cell manipulation. Currently, several anti-CD20xCD3 TCEs have demonstrated promising efficacy across different lymphoma subtypes with slightly better outcomes in the indolent subset. Anti-CD19xCD3 TCEs are being developed as well but only blinatumomab has been evaluated in clinical trials yet. The results are not so impressive as those with anti-CD19 CAR-T cell therapy. Antibody-drug conjugates targeting different B-cell antigens (CD30, CD79b, CD19) seem to be effective in combination with mAbs, standard chemoimmunotherapy, or immune checkpoint inhibitors. Further investigation will show whether immunotherapy alone or in combinatory regimens has potential to replace chemotherapeutic agents from the first line treatment.
Keywords: lymfoproliferativní nemoci; brentuximab vedotin; Immunotherapy; B-buněčný lymfom; monoklonální protilátky; imunoterapie; Humans; Immunoconjugates; zvířata; immunotherapy; polatuzumab vedotin; Lymphoma, B-Cell; imunokonjugáty; glofitamab; Animals; antibody-drug conjugates; Antibodies, Monoclonal; mosenutuzumab; lidé; bispecific antibodies; Lymphoproliferative Disorders; epcoritamab